2021
DOI: 10.21101/cejph.a6573
|View full text |Cite
|
Sign up to set email alerts
|

Annual influenza vaccination effect on the susceptibility to COVID-19 infection

Abstract: Objectives: We aimed to study the effect of seasonal influenza (flu) vaccination on the susceptibility to coronavirus disease 2019 (COVID-19). Methods: A total of 203 healthcare workers of a pandemic centre of Istanbul, Turkey, were included in this retrospective study. According to the presence or absence of flu vaccination, participants were divided into group 1 and group 2. A comparison of the rate of COVID-19 was done between these two groups. Also, the mean age and the sex ratio of females/males were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The findings also corroborate findings of studies that found similar protective effects for influenza vaccination [3][4][5][6][7][8][9][10][11][12] , though other studies did not 40,41 . These findings may be explained by influenza vaccination triggering a nonspecific immune activation, or trained or bystander immunity that is protective against SARS-CoV-2 infection [3][4][5]7,[42][43][44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings also corroborate findings of studies that found similar protective effects for influenza vaccination [3][4][5][6][7][8][9][10][11][12] , though other studies did not 40,41 . These findings may be explained by influenza vaccination triggering a nonspecific immune activation, or trained or bystander immunity that is protective against SARS-CoV-2 infection [3][4][5]7,[42][43][44][45][46][47] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have suggested a possible protective effect of the influenza vaccine against SARS-CoV-2 [9][10][11][12]. Although no cross-reactivity between influenza-induced antibodies and SARS-CoV-2 protection has been demonstrated, several theorized mechanisms of the potential protective effect of influenza vaccination have been proposed in the recent literature [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies enrolled individuals from the general population. Among them, five studies had as a population study health workers [2630], one study involved only pregnant women [31], another study included only transplant recipients [32] and four studies were performed in older adults (age >65) [3336]. The laboratory method (rt-PCR) used to diagnose of the disease was common in most of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two studies (Debisarum et al [37], Erismis et al [30]) were scrutinized further as in their analysis they used only age and sex, respectively as adjustment variables. However, when both were excluded from the meta-analysis and the overall meta-analysis was repeated, the results did not differ from the overall estimate: OR 0.81 (95% CI: 0.75-0.87).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation